Optimization of the Ohmic Process Effect for Garcinia Compote - Chooprajong, Sirinat; Binhayeeniyi, Nawal; Noitubtim, Madeena (Princess of Naradhiwas University Journal, 2021)
General Garcinia compote is carried on for a long time because the process of absorbing sugar through cell membranes and cell walls is slow. Therefore, ohmic heat is shown as one choice to decrease this period. This is because it uses voltage to cause pores on the cell wall and cell membrane, and it can be monitored by measuring the increased electrical conductivity of the cell. This research was to study the suitable condition of ohmic heat with Garcinia compote. The varieties of electric potential as 25, 50, 75, 100 and 125 V were applied to study the effects of voltage, time and temperature on electrical conductivity of garcinia cells. Garcinia was soaked in 3 concentrations of sucrose solution as 40, 50 and 60 ๐Brix for 24 hours. The results shown that the optimum voltages with 125 volts, 2 minutes duration, brought to 45 ๐C, and the Garcinia can be absorbed most in 24 hours with the concentration of sugar solution at 60 degrees brix.